A review on compatibility between crumb rubber and asphalt binder. (23rd August 2021) - Zheng, Wenhua; Wang, Hainian; Chen, Yu; Ji, Jie; You, Zhanping; Zhang, Yuqing
Highlights: This synthesis reviewed previous studies about compatibility between CR and asphalt. The interaction of CR-asphalt binder involves CR swelling and chemical degradation. Rheological methods are the most widely used methods for compatibility evaluation. Alternative measures can enhance the compatibility of rubberized asphalt binder. Desired compatibility means CR can be linked with asphalt and evenly distributed. Abstract: The compatibility between crumb rubber (CR) and asphalt binder plays a key role in the storage stability and rheological performance of rubberized asphalt binder. This review provides a comprehensive overview of characteristics of rubberized asphalt binder, factors influencing compatibility, compatibility evaluation methods, and improvement approaches. Desired compatibility results from the fact that CR is cross-linked with molecules of asphalt binder and evenly distributed in the asphalt binder, forming a homogeneous system. Rheological methods are the most widely used methods for compatibility evaluation. Additionally, the hybrid processing of surface activation treatment of CR and additives-grafting has shown to be a promising method for improving the compatibility of rubberized asphalt binder.